2019
DOI: 10.6004/jnccn.2018.7269
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Body Radiation Therapy Versus Nonradiotherapeutic Ablative Procedures (Laser/Cryoablation and Electrocautery) for Early-Stage Non–Small Cell Lung Cancer

Abstract: Background: Despite the fact that stereotactic body radiation therapy (SBRT) is the only recommended first-line therapy for inoperable early-stage non–small cell lung cancer (NSCLC), several thermal ablative procedures (TAPs; defined herein as laser/cryoablation and electrocautery) are available. Studies showing outcomes of these procedures and how they compare with SBRT are scarce. We sought to evaluate the comparative efficacy of SBRT versus TAPs using the National Cancer Database (NCDB). Methods: The NCDB w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Similar frequencies were noted in smaller prospective studies (86,87,138). Larger series report a 30-day mortality of 0.3-0.5% (134)(135)(136); but 90-day mortality was 3.8% in a large study (NCDB, 2004-14, 1,009 ablation patients) (139).…”
Section: Short-term Outcomes Treatment-related Toxicitysupporting
confidence: 69%
See 1 more Smart Citation
“…Similar frequencies were noted in smaller prospective studies (86,87,138). Larger series report a 30-day mortality of 0.3-0.5% (134)(135)(136); but 90-day mortality was 3.8% in a large study (NCDB, 2004-14, 1,009 ablation patients) (139).…”
Section: Short-term Outcomes Treatment-related Toxicitysupporting
confidence: 69%
“…Adjusted NRCs (Table 7 and Figure S4-6) (59,(139)(140)(141)(142)(143)(144)(145)(146)(147)(148)(149) demonstrate worse long-term outcomes after ablation than resection. The differences appear larger than for SBRT vs. resection (Table 1), but studies are limited and residual confounding makes interpretation difficult.…”
Section: Long-term Outcomes Survivalmentioning
confidence: 99%
“…20 It provides improved local control and overall survival (OS) compared with conventionally fractionated radiotherapy 9 and thermal ablation therapies, such as cryoablation and radiofrequency ablation. 25,26 Unfortunately, SBRT-related toxicity is higher in patients with ILD, and higher toxicity risk often correlates with higher ILD-GAP scores. A systematic review of mostly retrospective series reported an average incidence of grade greater than or equal to 3 radiation pneumonitis of 25% and treatment-related mortality of 16%.…”
Section: Sbrt In Patients With Ildmentioning
confidence: 99%
“…However, a retrospective comparison between various thermal ablation techniques and SBRT for stage I NSCLC using data from the National Cancer Database (NCDB) found no significant difference in overall survival rate but a higher rate of adverse effects in thermal ablation patients [31]. Another study using the NCDB reported a slightly lower overall survival rate for stage I NSCLC treated with various thermal ablation techniques compared to SBRT (33.5 vs. 37.7 months) [32]. Because of how ablations are coded in the NCDB, the studies could not determine outcomes for each of the techniques individually, which may vary significantly (Table 1).…”
Section: Non-small Cell Lung Cancermentioning
confidence: 99%